New Social Movements and Video Activism in the Context of Choreography of Assembly - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2018)
The shift from materialist values to post-materialist values in the capitalist system has brought a number of changes on the purpose and structure of social movements. However, in every period of history, the only essential thing for all social movements is the effective use of media tools. Depending on their differentiation, media tools, which are at a key point for gathering of social movement actors, lead to a number of transformations in the way social movements organize. Today, new media as the most suitable medium in the conditions of the period; parallel to their multi-tiered structure, has made it possible for individuals with different social backgrounds and expectations to act together against social problems. In this study; it is aimed to reveal the role of video in the process of organizing social movements via social media. In this sense, explaining the concept of video activism through the theory of Paolo Gerbaudo, who conceptualizes the process as choreography of assembly, the motivational potential of video to move people together against common problems will be emphasized through the Gezi Park protests.
Keywords: Media; Social Movements; Video Activism; Digital Activism; Choreography of Assembly; The Gezi Park Protests